Improving the flotation recovery of Cu from flash smelting slags by utilizing cellulose-based frother formulationss. (15th May 2022) - Nuorivaara, Ted; Klemettinen, Anna; Serna-Guerrero, Rodrigo
Graphical abstract: Highlights: First published study using polymer-surfactant mixes as frothers in Cu slag flotation. Using the PS-mix improved overall Cu recovery compared to commercial frother. PS-mix significantly increased productivity, i.e. similar froth product in less time. PS-mix demonstrated superior tolerance in performance when reducing xanthate dosage. Abstract: Froth flotation is an operation currently used for the recovery of Cu from pyrometallurgical smelting slags due its simple operation and relatively low operational costs. While it has been utilized for many decades, it may be necessary to develop strategies that improve Cu recovery from slags, as the unprecedented increase in Cu demand has made industrial waste and side streams economically relevant sources of metals. This study presents a novel chemistry-based approach for the flotation of Cu from smelting slags by utilizing an amphiphilic cellulose-surfactant mixture as a flotation frother, hereby referred to as CellFroth. The present work pursues two main objectives: i) to improve the performance of flotation for the treatment of smelting slags and ii) to accomplish a first proof of concept for frothers produced from renewable sources in the context of industrial waste treatment. The flotation performance of CellFroth was compared with a commercially available additive (i.e., DowFroth250) and hydroxypropyl methyl cellulose (HPMC). The results showed significant advantages in performance for CellFroth. At the highest collector concentration, Cu recovery was higher with CellFroth compared to DowFroth 250 and pure HPMC (73%; 62% and 65% respectively). A 75% reduction in xanthate concentrations had negligible effects on Cu recovery for CellFroth (70%), while recoveries decreased drastically with DowFroth250 (47%) and pure HPMC (50 %). Finally, CellFroth consistently reached comparable concentrate productivity (grade and recovery) as DF250 within significantly shorter flotation times. The use of CellFroth thus offers the possibility of increasing the Cu recovery from flash smelting slags, while reducing the environmental impact of the process by using a frother produced from sustainable sources and simultaneously reducing xanthate consumption.